2002
DOI: 10.1097/00000542-200209000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of the Effects of Single-dose Gabapentin versus  Placebo on Postoperative Pain and Morphine Consumption after Mastectomy

Abstract: A single dose of 1,200 mg oral gabapentin resulted in a substantial reduction in postoperative morphine consumption and movement-related pain after radical mastectomy, without significant side effects. These promising results should be validated in other acute pain models involving central neuronal sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
194
5
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(223 citation statements)
references
References 28 publications
13
194
5
4
Order By: Relevance
“…It has been shown that a reduction in morphine requirements of approximately 30% would be clinically significant. [12][13][14] Based upon results of previous studies with comparable designs, a standard deviation of 20 mg in the placebo group was predicted. 14 A mean cumulative morphine requirement of 60 mg in the placebo group, and 42 mg in the active treatment group was assumed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a reduction in morphine requirements of approximately 30% would be clinically significant. [12][13][14] Based upon results of previous studies with comparable designs, a standard deviation of 20 mg in the placebo group was predicted. 14 A mean cumulative morphine requirement of 60 mg in the placebo group, and 42 mg in the active treatment group was assumed.…”
Section: Discussionmentioning
confidence: 99%
“…During the postoperative period, no significant difference was seen between the two groups with respect to pain levels or morphine administration. 96 …”
Section: Gabapentinmentioning
confidence: 99%
“…Both drugs, in earlier clinical trials, have been used as a preemptive analgesic and found to be safe and effective. [3][4][5]12,13 The preemptive administration of gabapentin and tramadol approximately two hours before surgery appears rational in order to attain maximal plasma concentrations at the time of surgical stimuli. It has also been demonstrated that a single dose of 600 mg of gabapentin added to 60 mg slow release morphine increases pain tolerance to the cold pressure test in humans.…”
Section: Méthodementioning
confidence: 99%